Same inequities or engaged te tiriti partnership? - Kukutai, T.; McIntosh, T.; Moewaka Barnes, H.; McCreanor, T. (MAI Journal, 2020)
Keywords: community; covid-19; treaty obligations

The COVID 19 domestic vaccine pass: Implications for Māori - Kukutai, T.; Clark, V.; Mika, J.; Muru-Lanning, M.; Pouwhare, R.; Sterling, R.; Teague, V.; Watts, D.; Cassim, S. (National Institute of Demographic and Economic Analysis, University of Waikato, Aotearoa New Zealand, 2021)
The New Zealand government has introduced a COVID-19 domestic vaccine pass to be used in conjunction with the COVID-19 Protection Framework. The Framework is likely to be activated soon after Cabinet meets on 29 November 2021. The pass will be necessary to access places and events that require proof of vaccination under the Framework. This brief does not argue for or against the introduction of a domestic vaccine pass, but rather discusses key issues that it raises for Māori, and suggests actions to address them. We see four key issues: • the lack of Māori involvement, as a Tiriti partner, on either the design or implementation of the COVID-19 domestic vaccine pass; • disproportionate restriction on Māori mobility due to lower Māori vaccination rates; • privacy and data security concerns; • uneven implementation that could increase discrimination against Māori and other groups considered to pose a risk to others’ safety. To respond to these issues we recommend that the implementation of the pass be designed in partnership with Māori and comply with Māori data sovereignty requirements. As Tiriti partners, Māori should expect that the pass will keep their communities safe, while providing opportunities to enact manaakitanga in the matrix of care, and the mana to manage their own affairs.
Keywords: covid-19; data collection; data sovereignty; privacy; tiriti o waitangi/treaty of waitangi; treaty obligations